Axonal Patterns and Targets of dA1 Interneurons in the Chick Hindbrain - Kohl, Ayelet (J Neurosci, 2012)
Hindbrain dorsal interneurons that comprise the rhombic lip relay sensory information and coordinate motor outputs. The progenitor dA1 subgroup of interneurons, which is formed along the dorsal-most region of the caudal rhombic lip, gives rise to the cochlear and precerebellar nuclei. These centers project sensory inputs toward upper-brain regions. The fundamental role of dA1 interneurons in the assembly and function of these brainstem nuclei is well characterized. However, the precise en route axonal patterns and synaptic targets of dA1 interneurons are not clear as of yet. Novel genetic tools were used to label dA1 neurons and trace their axonal trajectories and synaptic connections at various stages of chick embryos. Using dA1-specific enhancers, two contralateral ascending axonal projection patterns were identified; one derived from rhombomeres 6–7 that elongated in the dorsal funiculus, while the other originated from rhombomeres 2–5 and extended in the lateral funiculus. Targets of dA1 axons were followed at later stages using PiggyBac-mediated DNA transposition. dA1 axons were found to project and form synapses in the auditory nuclei and cerebellum. Investigation of mechanisms that regulate the patterns of dA1 axons revealed a fundamental role of Lim-homeodomain (HD) proteins. Switch in the expression of the specific dA1 Lim-HD proteins Lhx2/9 into Lhx1, which is typically expressed in dB1 interneurons, modified dA1 axonal patterns to project along the routes of dB1 subgroup. Together, the results of this research provided new tools and knowledge to the assembly of trajectories and connectivity of hindbrain dA1 interneurons and of molecular mechanisms that control these patterns.